HUBUNGAN DURASI PENGGUNAAN MEDIA SOSIAL, KADAR HEMOGLOBIN, ASUPAN MAKAN, DAN SOSIAL EKONOMI DENGAN PRESTASI BELAJAR SISWA DI SMA BUDHI WARMAN II JAKARTA - Rizka Amelia (2023)
Background: Based on the result of PISA 2018, Indonesia's academic achievement among students is still below the global's average score. The low academic achievement is a reflection of a low human resources quality and this will affect on the difficulty to compete with other country. There are two factors that affects student's academic achievement, an internal and external factor. Objective: To determine the relationship of social media usage time, hemoglobin level, food intake, and social-economic to student's academic achievement of SMA Budhi Warman II Jakarta. Method: This study used a cross-sectional study design with quantitative method that involves 109 respondents from grade X and XI. Purposive sampling was the sampling method that is used on this study. Result: There is a relationship between academic achievement on reading with hemoglobin level and energy intake (p value = 0,000 and 0,033). There is a relationship between academic achievement on math with energy intake (p value = 0,016). There is no relationship between social media usage time and social-economic with student's academic achievement. Conclusion: Student's academic achievement have a relation to hemoglobin level and food intake. Keyword: Academic Achievement, Food Intake, Hemoglobin Level, PISA, Social-Economic, Social Media Usage Time